Characteristics of Maxilofacial Fractures That Entered the ER at Dr. Mohammad Hoesin General Hospital Palembang Period 1 January 2019 - 31 December 2019 - Bram Permadi Tant; Abda Arief (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2021)
Background: Maxillofacial trauma is a wound or injury that affects the face and jaw.1 Trauma to the hard tissues of the face can cause maxillofacial fractures, which is damage or breaking of the continuity of the facial bones. Traffic accidents remain the main cause of maxillofacial injury, followed by violence, sports, work-related injuries, and falls 9,10,11,12 The high number of traffic accidents and violence in Palembang city can increase the risk of maxillofacial fracture. The absence of data regarding the characteristics of patients with maxillofacial fractures at Dr. Mohammad Hoesin General Hospital Palembang became the reason for this research. Methods: This research is a descriptive observational study with a cross sectional design using secondary data through patient medical records for the period January 2019- December 2019. Results: There were 89 patients with maxillofacial fractures with complete medical record data. There were more men (83.14%) than women (16.85%). The youngest age of the patient was 7 years, while the oldest age was 70 years, with the mean age of the patient was 29 years. Traffic accidents were the most common cause (79.7%) followed by falls (11.2 %), violence (4.4 %), sports accidents (1.1 %), and other causes (3.3%). 28 fracture locations were recorded on the upper face, 55 with fracture locations at the midface, 26 with fracture locations on the lower face. The zygomaticomaxillaris complex fracture was the most common fractured bone (35.9%). Regarding management, most were managed with ORIF (66.2%) followed by elevated craniotomy (16.85%), conservative (12.35%), soft tissue debridement repair (2.2%) and closed reduction and nasal repositioning (2.2%). Conclusion: Maxillofacial fracture are found commonly in men. Most patient age ranges. is the age of 21-30 years. The most common cause is traffic accidents. The most frequently affected fracture site is the midface, where the most commonly affected bone is the zygomaticomaxillaris complex. The treatment option most often applied is ORIF.